Social Choice Theory: A Neglected Path to Possibility - Korpela Ville (Aboa Centre for Economics (ACE), 2016)
Often preferences of agents are such that any sensible goal of the collective must admit a tie between all alternatives. The standard formulation in mechanism design demand that in this case all alternatives are equilibrium outcomes of the social choice mechanism. However, as far as the idea of an equilibrium is to predict the outcome of a game, we could just as well demand that there are no equilibria at all. Although this may seem innocent, and in a technical sense that's right, it is a neglected path to possibility.
Keywords: C72; D71; 330; Condorcet Criterion; Collective Decision Making; Implementation; Impossibility Result; Nash Equilibrium; Social Choice Theory